Influence of residential characteristics and preferences on residential satisfaction among young households in unplanned neighbourhoods in Kano, Nigeria - Abdu, Ado (2015)
The main objective of the study was to examine the influence of residential characteristics and preferences on residential satisfaction among young households in unplanned neighbourhoods in Kano, Nigeria. Three and sixty eight (368) young households whose heads aged 45 years and below who moved to unplanned neighbourhoods within the period of three to five years in Kano Metropolis were selected as respondents for this study. This study employed multistage cluster sampling to select three unplanned neighbourhoods namely; Wailari, Dorayi-Karama and Gama E and systematic random sampling was utilized to select the respondents. A questionnaire survey was adapted from previous studies for the data collection and the researcher and trained enumerators collected the data. The questionnaire consisted of questions on previous and current neighbourhoods regarding household and residential characteristics and residential satisfaction and residential preferences. Data analysis utilized descriptive statistics such as percentages and Yeh’s Index of Satisfaction and inferential statistics such as Pearson’s correlation, multiple regression and mediation analyses. Results of descriptive statistics of the socioeconomic and demographic characteristics showed that the respondents had mean age of 39 years, 6 household members, majority had formal education and owned single family houses (attached) with 3 - 4 rooms, and lived there for 4 - 5 years. The results of Yeh’s Satisfaction Index (YIS), revealed that the respondents had very low (dissatisfied) to low levels of satisfaction with almost all the items and residential characteristics components (housing features, housing conditions, neighbourhood facilities and neighbourhood accessibility) for previous neighbourhoods. For the current neighbourhoods, the respondents had high levels of satisfaction with almost all the items and the previous residential characteristics components. Correlations between socioeconomic and demographic characteristics, previous residential characteristics, residential preferences and satisfaction were investigated. The result indicated age of respondents; household income, household size,tenure (renter), tenure (owner) number of bedrooms and number of rooms, had significant relationship with the current residential satisfaction. Other factors with significant relationship with current residential satisfaction were previous neighbourhood facilities, housing features preference, housing amenities preference, housing conditions preference, housing safety, and security preference, neighbourhood facilities preference, neighbourhood amenity preference, and neighbourhood accessibility preference. However, length of residence, previous housing features, previous housing conditions, and previous neighbourhood accessibility did not have a significant relationship with the current residential satisfaction. The results of multiple regression analysis on the factors that contribute to the current residential satisfaction of the respondents indicated that five predictor variables explained 46.5% of the variance in the current residential satisfaction. These variables were age of respondents (β =.146, t = 3.272, p =.001) and total number of rooms (β =.165, t = 3.297, p =.001). Other significant factors also included housing features preference (β =.331, t = 7.225, p =.000), housing conditions preference (β =.111, t =2.264, p =.024) and neighbourhood amenities preference (β =.203, t = 2.963, p =.003). The model did not show significant contributions of household size, household monthly income, tenure (owner), tenure (renter), total number of bedrooms, previous neighbourhood facilities, housing amenities preference, housing safety and security preference and, neighbourhood facilities preference, and neighbourhood accessibility preference to the current residential satisfaction of the respondents. The result of moderation analysis using the bootstrapping method indicated that there was a significant indirect mediating effect of residential preference on the relationship between previous residential characteristics and current residential satisfaction. Based on these findings, it can be concluded that socioeconomic and demographic characteristics and some residential preference components had significant influence on residential satisfaction among young households in unplanned neighbourhoods in Kano, while previous residential characteristics had little contribution to their residential satisfaction. Findings on the mediation role of residential preference have an implication of the need to provide housing that satisfied their needs and preference. Thus, policy makers and planners have to consider housing features preference and amenities preference of young households for planned housing decisions.